Affordability of battery electric vehicles based on disposable income and the impact on provincial residential electricity requirements in South Africa. (15th March 2019) - Pillay, N.S.; Brent, A.C.; Musango, J.K.
Abstract: South Africa's political history, unique demographic profile, and economic growth drivers, present a challenge in adopting universal strategies and business models to plan for the impact of battery electric vehicles in the residential sector. This paper investigated battery electric vehicle (BEV) substitution of internal combustion engine vehicles (ICEVs) on a provincial level, to better plan for additional electricity requirements. This was achieved by developing the E-StratBEV model, using system dynamics. The model results show that nationally, although the Low Growth scenario indicates about 233, 700 BEVs by 2040, the adjusted number (based on the spending behaviour within deciles) may result in 44, 155 BEVs while the High Growth scenario's expected 2.39 million BEVs by 2040 could be adjusted down to 451, 736 BEVs. For a coal heavy supply mix, the cumulative carbon emissions from 2019 until 2040 resulted in negligible benefits, so provinces may not be able to leverage on passenger electric vehicles to reduce provincial environmental emissions. Lastly, the BEV growth drivers introduced an additional 1589 BEVs to the Low Growth scenario and an additional 16, 257 BEVs to the High Growth targets from 2019 to 2040, with the purchase price being the dominant driver. Highlights: Households may purchase 80% less than expected passenger EVs. Negligible benefits for passenger EVs to reduce environmental carbon emissions. Reducing purchase price has the biggest impact to increase EV sales.